Microtopography mediates the climate–growth relationship and growth resilience to drought of Pinus tabulaeformis plantation in the hilly site - Zhao, Hongming; Wu, Jiabing; Wang, Anzhi; Guan, Dexin; Liu, Yage (Frontiers in Plant Science, 2022)
Plantations spread widely in hilly regions, but the effect of micro-topography on growth was studied little. We selected the Pinus tabulaeformis planted in hilly site, and studied the effect of micro-topography on climate-growth relationship and drought response of typical plantation in Northeast China using dendroecological methods. We found: 1) Between hill-positions, temperature caused the climatic growth difference. Compared to on hillside, the correlation of annual growth on hilltop with monthly temperature was less negative in July-August and more positive in January-April. 2) Between aspects, precipitation intensities caused the climatic growth difference. Compared to on shady slope, the correlation of annual growth on sunny slope with monthly total precipitation below 10 mm/d was more positive (May-June) or less negative (March-April and July), while that with monthly total precipitation above 10 mm/d was less positive in most months. 3) Drought response varied significantly based on hill-position and aspect. No significant difference in resistance between hill-positions, while recovery and resilience on hilltop were greater than those on hillside. Resistance, recovery, and resilience were all lower on sunny slope than on shady slope. Differences in recovery and resilience reflected the legacy effect of drought on different micro-topography, which could lead to subsequent changes in climate-growth relationships. These findings demonstrate that strengthening the research of forest trees on micro-topography is necessary for accurate carbon sink assessment and precise forest management.